2014
DOI: 10.1016/j.ecoenv.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxicological risk of foodstuffs contaminated with heavy metals in Swat, Pakistan

Abstract: a b s t r a c tThis study aimed to assess the concentrations of heavy metals such as cadmium (Cd), chromium (Cr), copper (Cu), manganese (Mn), nickel (Ni), lead (Pb) and zinc (Zn) in the available foodstuffs (crops, milk and water), their bioaccumulation in human body and potential human health risks in Swat valley, northern Pakistan. Heavy metal concentrations in foodstuffs and human blood (adults (18-above) and children (1-12 years)) were analyzed using atomic absorption spectrometer. The results revealed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 31 publications
1
22
5
Order By: Relevance
“…The mean values found in this research were higher than reported by Simsek, Gultekin, Oksuz, and Kurultay () in heavy traffic areas of Turkey (0.58 ppm), Licata et al () in Calabria in Italy (0.00198 ppm), Patra et al () in India (0.101 ppm), Rodríguez, Sanz, and Díaz () (0.076 ppm), Tripathi, Raghunath, Sastry, and Krishnamoorthy () (0.195 ppm), Onianwa, Adetola, Iwegbue, Ojo, and Tella () (0.67 ppm), Lante, Lomolino, Cagnin, and Spettoli () (0.0518 ppm), Enb, Donia, Abd‐Rabou, Abou‐Arab, and El‐Senaity () (cow = 0.212 ppm and buffalo = 0.142 ppm), Khan et al () in Swaat Valley, Pakistan (0.164 ppm) in northern (0.9319 ppm) and southern (0.8484 ppm) regions of Croatia, Birghila, Dobrinas, Stanciu, and Soceanu () in cow milk (0.17 ppm), Maas et al () in cow milk (0.28 ppm). The concentration of Cu found in this research were lower than found by Younus et al () in Pakistan (Jhang District) (1.354 ppm) with range of 0.5 ppm to 3.229 ppm.…”
Section: Resultscontrasting
confidence: 67%
“…The mean values found in this research were higher than reported by Simsek, Gultekin, Oksuz, and Kurultay () in heavy traffic areas of Turkey (0.58 ppm), Licata et al () in Calabria in Italy (0.00198 ppm), Patra et al () in India (0.101 ppm), Rodríguez, Sanz, and Díaz () (0.076 ppm), Tripathi, Raghunath, Sastry, and Krishnamoorthy () (0.195 ppm), Onianwa, Adetola, Iwegbue, Ojo, and Tella () (0.67 ppm), Lante, Lomolino, Cagnin, and Spettoli () (0.0518 ppm), Enb, Donia, Abd‐Rabou, Abou‐Arab, and El‐Senaity () (cow = 0.212 ppm and buffalo = 0.142 ppm), Khan et al () in Swaat Valley, Pakistan (0.164 ppm) in northern (0.9319 ppm) and southern (0.8484 ppm) regions of Croatia, Birghila, Dobrinas, Stanciu, and Soceanu () in cow milk (0.17 ppm), Maas et al () in cow milk (0.28 ppm). The concentration of Cu found in this research were lower than found by Younus et al () in Pakistan (Jhang District) (1.354 ppm) with range of 0.5 ppm to 3.229 ppm.…”
Section: Resultscontrasting
confidence: 67%
“…The adsorption edge experiments were conducted under atmospheric conditions at different solution pH (3)(4)(5)(6)(7)(8)(9)(10), total Cr(VI) concentrations (10 -4 , 10 -5 , and 10 -6 M) and ionic strengths (using 0.001, 0.01, and 0.1 M KNO3 as the background electrolyte). Ferrihydrite (2 g/L), birnessite (20 g/L), kaolinite (20 g/L), and illite (20 g/L) were added to the 500 mL solution containing Cr(VI) and the background electrolyte.…”
Section: Samples For Adsorption Modelingmentioning
confidence: 99%
“…The environmental, toxicological, and health risks associated with Cr(VI) are closely linked to its speciation and behavior in the environment [4][5][6]. Therefore, there is a need for understanding the adsorption of Cr(VI) at the solid-soil solution interface, which is a major factor in determining its distribution [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo drinking water had higher trace element concentrations than those of cows and goats. Buffalo drinking water samples were collected from different province; therefore, region might account for such differences [31,32]. The concentrations of V, Co, Ni, Cu, Ga, Se, Rb, and Cs in drinking water were lower than 10 μg/L; Ag was not detected in any of the samples.…”
Section: Concentrations Of Trace Elements In Drinking Water and Feed mentioning
confidence: 99%